Semantic features of polysemous words in folk dialects (based on the material of the middle and Western dialects of the Tatar language) - Bulatova, Alfiya K.; Bulatova, Minnira R. (The New Research of Tuva, 2025)
The article analyzes the semantic features of polysemous words in the folk dialects of the Tatar language, based on the materials of the Central and Western dialects. The study of polysemy in dialects is relevant not only to linguistics but also to the preservation of cultural heritage, the understanding of language evolution, and the development of modern technologies. The authors examine the specificity of polysemy in dialectal vocabulary, identifying key patterns in the formation and functioning of polysemous units. Examples are provided with words that acquire unique meanings in different dialectal regions, reflecting the cultural, historical, and everyday features of the area. Special attention is given to the interaction between dialectal polysemy and literary language, as well as the influence of interlingual contacts on the semantic structure of words. The polysemy of dialectal verbs is conditioned by local cultural, every day, and ritual practices, which contributes to the emergence of unique semantic nuances and lexico-semantic variants that are not characteristic of the literary language. The dialects preserve meanings associated with the traditional culture and way of life of the Tatars in the studied regions. It is shown that in the analyzed dialects, there is a semantic expansion of lexical units that reflect local rituals and customs. The speech of dialect speakers retains a distinctive ethnocultural vocabulary. Most dialectal verbs are characterized by polysemy, which is realized through semantic expansion and narrowing, as well as semantic shifts within individual dialects and across dialect groups. The study reveals not only the preservation of archaic semantic elements but also the active development of new meanings and the dynamics of semantic boundaries of verbs in the form of expansion or narrowing. These processes contribute to a better understanding of the mechanisms of semantic evolution and the importance of dialects in preserving linguistic heritage.